Tripartite interactions comprising yeast-endobacteria systems in the gut of vector mosquitoes - Cappelli, Alessia; Damiani, Claudia; Capone, Aida; Bozic, Jovana; Mensah, Priscilla; Clementi, Emanuela; Spaccapelo, Roberta; Favia, Guido; Ricci, Irene (Frontiers in Microbiology, 2023)
It is shown that bacteria use yeast as a niche for survival in stressful conditions, therefore yeasts may act as temporary or permanent bacterial reservoirs. Endobacteria colonise the fungal vacuole of various osmotolerant yeasts which survive and multiply in sugar-rich sources such as plant nectars. Nectar-associated yeasts are present even in the digestive system of insects and often establish mutualistic symbioses with both hosts. Research on insect microbial symbioses is increasing but bacterial-fungal interactions are yet unexplored. Here, we have focused on the endobacteria of Wickerhamomyces anomalus (formerly Pichia anomala and Candida pelliculosa), an osmotolerant yeast associated with sugar sources and the insect gut. Symbiotic strains of W. anomalus influence larval development and contribute digestive processes in adults, in addition to exerting wide antimicrobial properties for host defence in diverse insects including mosquitoes. Antiplasmodial effects of W. anomalus have been shown in the gut of the female malaria vector mosquito Anopheles stephensi. This discovery highlights the potential of utilizing yeast as a promising tool for symbiotic control of mosquito-borne diseases. In the present study, we have carried out a large Next Generation Sequencing (NGS) metagenomics analysis including W. anomalus strains associated with vector mosquitoes Anopheles, Aedes and Culex, which has highlighted wide and heterogeneous EB communities in yeast. Furthermore, we have disclosed a Matryoshka-like association in the gut of A stephensi that comprises different EB in the strain of W. anomalus WaF17.12. Our investigations started with the localization of fast-moving bacteria-like bodies within the yeast vacuole of WaF17.12. Additional microscopy analyses have validated the presence of alive intravacuolar bacteria and 16S rDNA libraries from WaF17.12 have identified a few bacterial targets. Some of these EB have been isolated and tested for lytic properties and capability to re-infect the yeast cell. Moreover, a selective competence to enter yeast cell has been shown comparing different bacteria. We suggested possible tripartite interactions among EB, W. anomalus and the host, opening new knowledge on the vector biology.